The Critical Innovation Discourse of Small VODs: The Case of The Death of Mr. Lăzărescu on Cinepub - Parvulescu, Constantin (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
My article compares the catalogues and interfaces of a small and a big VOD provider and emphasizes the critical innovative potential of the intervention of the former and, more generally, of small streaming services. I employ a cultural studies approach and closely read the acts of curation of these two types of providers. As a case study, I focus on the curation of the feature film The Death of Mr. Lăzărescu on both platforms. By critical innovation, I understand an economic or industrial intervention that questions and disrupts hegemonic discourses in its field. In the case of VODs, it refers to an engagement with discourses on digital film consumption, the branding of premium content, establishment of taste, and diversity of content. I also approach critical innovation as political and economic. I provide proof that small non-profit providers set up more advantageous viewing experiences that benefit a film and its makers. I also show that they play an important role in maintaining the sustainability of a digital distribution ecosystem.